Relevance of Visual Acuity Measurement for Therapeutic Decisions in Diabetic Macular Edema - Thibaud Mathis; Batoul El Ameen; Cristina Vartin; Yasmine Serrar; Frédéric Matonti; Aditya Sudhalkar; Alper Bilgic; Amina Rezkallah; Laurent Kodjikian (MDPI AG, 2023)
This study aimed to determine the validity of basing retreatment decisions on anatomical criteria alone (captured using optical coherence tomography (OCT)-OCT-guided strategy) rather than the gold standard (combined visual acuity (VA) and OCT) in patients with diabetic macular edema (DME). This cross-sectional study included 81 eyes undergoing treatment for DME from September 2021 to December 2021. An initial therapeutic treatment decision based on OCT results was made on inclusion. Subsequently, in light of the patient's VA score, this initial decision was upheld or adjusted, and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. In 67 out of the 81 eyes included in the study (82.7%), the OCT-guided strategy produced equivalent results to the gold standard. In this study, the OCT-guided retreatment decision strategy yielded sensitivity and specificity of 92.3% and 73.8%, respectively, and PPV and NPV of 76.6% and 91.2%, respectively. These findings differed according to the patient's treatment regimen: the sensitivity and specificity for eyes under a treat and extend regimen was higher, 100% and 88.9%, respectively, than eyes under a Pro Re Nata regimen, 90% and 69.7%, respectively. These findings show that VA testing could be omitted from the follow-up of certain patients with DME treated with intravitreal injections without impacting the quality of care.